Pendampingan Pembuatan dan Penggunaan Alat Peraga Dakota Pada Pembelajaran FPB dan KPK - Ana Istiani; Yunni Arnidha (Publikasi Pendidikan, 2018)
The application of character learning to elementary mathematics requires certain techniques. In the mathematics of elementary school teachers should use abstract media. Problems that arise in elementary school mathematics teacher in Kecamatan Negeri Katon is lack of knowledge in using props, in this case on FPB material and KPK. In addition, teachers are still confused in choosing the props that should be used on every learning material. To overcome this is used DAKOTA props that can facilitate students' understanding in learning FPB and KPK materials. The method used in this devotion is the making of DAKOTA props using rigid boards. From the results of this devotion activity obtained the spirit of mathematics teachers and the emergence of ideas to make props on other learning materials.